The Frescoes of the Haghpat Monastery in the Historical-Confessional Context of the 13th Century - Hakobyan, Zaruhi A. (Actual Problems of Theory and History of Art, 2021)
The Church of the Holy Sign of Haghpat monastery was built and painted by Bagratids. From this early layer of murals only the very small fragments have been preserved. During the second rise of the monastery under the Zacharids, when the Armenian-Chalcedonian community was on the rise, there was a demand for new frescoes, which were executed in two stages. Under the patronage of Zakare, as the sign of loyalty to the Orthodox, the Armenian-Chalcedonians were invited to decorate this non-Chalcedonian church and apparently they also worked on the sanctuary. These frescoes with bilingual inscriptions (typical for Orthodox Armenians) emerged before 1212. In the middle of the 13th century, after the earthquake, it became necessary to renovate the frescoes in the church, which was carried out already in the 1280s by the new patron of the monastery from the Artsrunid family, adhering to the Armenian National Church.
Keywords: Haghpat; Holy Sign; Armenian-Chalcedonians; Orthodox; iconography; Zakharids; Khutlubugha; Deesis; Eucharist; frescoes